2019
DOI: 10.1155/2019/9468451
|View full text |Cite
|
Sign up to set email alerts
|

Effects of In-Vehicle Navigation on Perceptual Responses and Driving Behaviours of Drivers at Tunnel Entrances: A Naturalistic Driving Study

Abstract: The perceptual responses and driving behaviours of drivers at tunnel entrances vary, which could cause interference and accidents. This study investigated the effects of in-vehicle navigation on the perceptual responses and driving behaviours and whether these effects are actually valid for safety improvement. For this purpose, a series of naturalistic driving experiments was conducted and a comparative analysis was performed considering two different experiment conditions, control condition and in-vehicle nav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…We cannot generalise our findings to all factors such as traffic volume, drivers' experience, and auxiliary driving condition. However, these factors are likely to have a major influence on driving behavior and visual perception [5,14,19].…”
Section: Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…We cannot generalise our findings to all factors such as traffic volume, drivers' experience, and auxiliary driving condition. However, these factors are likely to have a major influence on driving behavior and visual perception [5,14,19].…”
Section: Limitationmentioning
confidence: 99%
“…For example, the standard deviation of speed has been found to be positively correlated with crash rates, with differences in speed between positional zones corresponding to differences in zonal crash rates. Increasing the mean and maximum deceleration increases the tunnel entrance crash rate, while the vehicle lateral position has been shown to be a reliable indicator of risk of lateral crashing [2,6,13,19]. A number of derivative variables, such as time to collision [20,21], sight distance [5], and driving workload [1,22,23], have also been used to elucidate relevant tunnel entrance safety problems.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, ample studies have been conducted on the physiological indices and driving performance of drivers in tunnels. Fu et al concluded that in-car navigation has a significant influence on a driver’s perceptual response and driving behavior at tunnel entrances, and the influence degree was different in different regions [ 4 ]. By collecting eye movements (number of fixations, duration of fixations, and number of saccades) and driving performance (speed, steering wheel, and vehicle lateral position), Wang et al reported a gradual increase in the number of fixations, duration of fixations and number of saccades in the transition zone.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al established a regression model of the luminance, vehicle speed, and HR growth rate in the case of mountainous tunnels, focusing on the relationship between drivers' workload, luminance, and vehicle speed [10]. The above research focused on the influence of tunnel entrances and exits on both drivers' physiological indices and driving behavior through field or simulation experiments [4][5][6][7][8][9][10]. Some scholars only studied the influence of tunnels on the driving performance.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the role of signs and markings is degraded under adverse weather conditions, such as foggy weather. In-vehicle audio warning (IVAW) countermeasure based on intelligent vehicle infrastructure cooperative (IVIC) technology can make up for the defects of static signs and markings [19]. Many studies have confirmed that IVAW can improve driver behavior.…”
Section: Introductionmentioning
confidence: 99%